Tick Fauna and Associated Rickettsia, Theileria, and Babesia spp. in Domestic Animals in Sudan (North Kordofan and Kassala States) - Andrea Springer; Yassir Adam Shuaib; Makarim Habib Isaa; Malaz Isam-Eldin Ezz-Eldin; Abdinasir Yusuf Osman; Idris Ahmed Yagoub; Mohamed Abdalsalam Abdalla; Amel Omer Bakiet; Saad El-Tiab Mohmed-Noor; Sabine Schaper; Ramona Rieß; Gerhard Dobler; et al. (Microorganisms, 2020)
Ticks and tick-borne diseases (TBDs) have a major economic impact on animal production worldwide. In the present study, 2410 ticks were collected from January to August 2017 from livestock and other domestic animals in North Kordofan and Kassala, Sudan, for species identification and investigation of Rickettsia spp. and piroplasms, either individually or as pools containing up to 10 ticks by molecular methods. In total, 13 tick species were identified by morphology and 16S rDNA sequencing. The most frequent tick species were Hyalomma impeltatum (24.90%), Rhipicephalus evertsi evertsi (18.84%), Amblyomma lepidum (16.06%), and Rhipicephalus camicasi (12.49%). A pan-Rickettsia real-time PCR revealed an overall minimum infection rate (MIR) with Rickettsia spp. of 5.64% (136 positive tick pools/2410 total ticks). Rickettsia africae and Rickettsia aeschlimannii were the most frequently identified species by sequencing. Furthermore, the following highly pathogenic livestock parasites were detected: Theileria annulata, Theileria lestoquardi, Theileria equi, and Babesia caballi. The present study documented Rhipicephalus afranicus as well as Rickettsia conorii israelensis, Rickettsia massiliae, and Babesia pecorum for the first time in Sudan. These findings are significant for the animal production sector as well as in terms of One Health, as the detected Rickettsia spp. can cause serious illness in humans.